JOB PERFORMANCE OF SECONDARY SCHOOL TEACHERS DUE TO COVID-19 PANDEMIC (CASE STUDY IN IPOH, PERAK) - Rebecca Anthony Martin; Chong Mei Kuan; Pang ang Seo; Tajpreet Kaur a/p Lakhbir Singh; Thanaletchumi Letchumana; Kogilavani Apadore (Journal of Islamic, Social, Economics and Development, 2024)
This study looks at how the COVID-19 pandemic affected the performance of secondary school teachers in Ipoh, which is located in the state of Perak. The purpose of this study is to investigate the ways in which job performance is affected by work-family conflict, the working environment, and work-life balance. A total of 220 questionnaire surveys were collected from secondary school teachers in the selected region. The analysis, including Pearson's Correlation Coefficient and Multiple Linear Regression Analysis, indicates a significant association between the independent variables and job performance. The findings contribute to our understanding of the challenges faced by teachers during the pandemic and highlight the importance of addressing work-family conflict, improving the work environment, and promoting work-life balance to enhance job performance in the educational sector.